Mapping and quantifying deforestation in the Zambezi ecoregion of Central-Southern Africa: extent and spatial structure - Khoji Muteya, Héritier; N’tambwe Nghonda, Dieu-donné; Malaisse, François; Bogaert, Jan; Useni Sikuzani, Yannick (Frontiers in Remote Sensing, 2025)
IntroductionForests in the Zambezi ecoregion play a critical role in sustaining biodiversity and the livelihoods of over 100 million people across Southern and Central Africa. However, these forests face growing threats from human activities. This study assessed forest-cover changes at the national scale within the Zambezi ecoregion from 2000 to 2023.MethodsA total of 600 Landsat images acquired for the years 2000, 2008, 2016, and 2023 were used to analyze forest cover change. Forest cover was classified using the Random Forest algorithm, integrated with Geographic Information Systems (GIS) and landscape metrics to assess patterns of forest fragmentation and ecological transformation.ResultThe results showed a significant reduction in forest area from 2,328,377.5 km2 to 1,817,513 km2, corresponding to an annual deforestation rate of 0.95%. This decline was associated with a substantial decrease in the largest patch index, signifying increased fragmentation driven primarily by patch dissection and suppression. At the country level, annual deforestation rates above 1% were identified in Malawi (2.07%), Burundi (1.92%), Zimbabwe (1.57%), and Tanzania (1.06%), while lower rates were observed in Zambia (0.93%), Mozambique (0.92%), Angola (0.83%), and southeastern Democratic Republic of the Congo (0.72%). Despite widespread forest loss, some limited forest stability and regeneration offer potential for ecological restoration.DiscussionThe findings emphasize the increasing human-induced pressures on forests within the Zambezi ecoregion and highlight the urgent need for coordinated restoration initiatives by the Southern African Development Community (SADC). Crucial steps include engaging local communities in forest governance, promoting natural forest regeneration, and implementing sustainable agriculture and clean-energy policies to conserve biodiversity and maintain ecosystem services.